The role of vision in auditory distance perception - Calcagno, Esteban (2012)
In humans, multisensory interaction is an important strategy for improving the detection of stimuli of different nature and reducing the variability of response. It is known that the presence of visual information affects the auditory perception in the horizontal plane (azimuth), but there are few researches that study the influence of vision in the auditory distance perception. In general, the data obtained from these studies are contradictory and do not completely define the way in which visual cues affect the apparent distance of a sound source. Here psychophysical experiments on auditory distance perception in humans are performed, including and excluding visual cues. The results show that the apparent distance from the source is affected by the presence of visual information and that subjects can store in their memory a representation of the environ- ment that later improves the perception of distance.